An efficient resource allocation in strategic management using a novel hybrid method - Ratapol Wudhikarn (2018)
© 2016, © Emerald Group Publishing Limited. Purpose – The purpose of this paper is to suggest a novel hybrid method by integrating a decision sciences approach with balanced scorecard (BSC) in order to scientifically enable the efficient strategic management of an organization under limited resources. The proposed research model endeavors to improve critical basis deficiencies of the original BSC as well as formerly improved forms of BSC by appropriately integrating three disparate methods: BSC, analytic network process (ANP), and zero-one goal programming (ZOGP). Design/methodology/approach – The designed approach is separated into three major parts. At first, the traditional BSC, concentrating on both financial and intellectual capital, was adopted as the strategic management framework, and then priorities as well as the importance of tactical drivers derived from BSC application were consecutively identified by the application of ANP. Finally, the study further applied the obtained results of integrated BSC and ANP to ZOGP in order to scientifically identify the optimal strategic investment under simulated constraints of the considered organization. Findings – An application of BSC, ANP, and ZOGP with a case study of an academic institution provided an improved strategic management approach for optimally and scientifically utilizing the limited resources of the organization. The suggested results indicated that only 11 of the 23 strategic projects should be executed. Moreover, the selected tactical tasks would efficiently use less than 36 percent of the strategic expenses of the traditional management approach. Originality/value – Based on the intensive literature reviews, the proposed method could be determined as a novel hybrid approach. It newly conveyed the practical management approach by innovatively including the proper decision sciences method to BSC. This improvement scientifically considered on the resource allocation process that has never been studied before in formerly improved BSC.